One heart, two lungs... and two stomachs? An interesting case of a gastric duplication in a 15-year-old patient - Simoniuksztis, Anna; Nogal, Piotr; Sosnowska, Patrycja; Mańkowski, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Gastric duplication is a rare condition, which may manifest itself as a tumor in epigastrium. It should be taken into consideration during a differential diagnosis of lesions in this area. Presented here is a case of a 15-year-old boy operated due to this condition.